Monitoring the Geometry of Tall Objects in Energy Industry - Tadeusz Głowacki (Energies, 2022)
The landscape shaped by the energy industry is rich in various slender structures, such as smokestacks, cooling towers, and others. It is thus becoming increasingly important to effectively monitor the geometrical condition of all types of such structures. Slender structures are deformed elastically under loads due to wind. A proper analysis of the changes and deformations of such structures requires a continuous ground-based measurement system which allows the movement of the structure to be measured in two horizontal directions, from a significant distance and with a possibly reduced number of stations. For this purpose, two methods were implemented: a linear terrestrial laser scanning method (TLS) and an optical, direct distance measurement method—tachymetry (TCH). The least squares method was used to fit rings on various levels of the structure and then the centers of the rings were identified. The comparison of the identified ring centers enabled the axis of the structure to be measured for deviation in two perpendicular directions. The methods were verified on actual structures: a smokestack 110 m in height, a cooling tower 60 m in height, and a wind turbine with the rotor axis at 149 m. The measurement results were compared with respect to the measurement time and the obtained accuracies at which the point locations were identified on the structure. The proposed methods are an effective tool for monitoring the condition of slender objects both during their operating life and after it. Regular monitoring of the geometric condition of slender structures in the energy industry limits the risk of major or catastrophic events, and as a result allows the safe and uninterrupted delivery of electric energy to clients.